Development of branding concept and philosophy in establishing Malaysian fashion designers at the global market - Abd Karim, Khairulazlan; Shaari, Nazlina (2016)
The paper focuses on the development of brand concept and philosophy for the purpose of enabling Malaysian fashion designers to penetrate and establish themselves in the international fashion markets. The problem of the research is the lack of new Malaysian brands in the global market besides the few designers (Jimmy Choo and Zang Toi) who are already aging. The objective of the study is to produce a guideline or module that can be used by local fashion designers in preparing and developing their brands to the potential of establishing themselves in the international fashion scene. By identifying the factors affecting brand development and the segmentation of the global market, it is hoped that local designers will be able to focus their efforts to a specific target. The research methodology employs a qualitative data collection through interviews. Data analysis is carried out using Content Analysis. The conceptual framework is based on Healey’s Theory of Branding that includes five components that are positioning, storytelling, design, price and customer relationship. The expected result includes a database of local fashion designers, the identification of fashion trends in international markets, and determining the marketing strategies to venture into the global market. Benefits of the study include identifying the factors that affect Malaysian fashion designers from venturing into the fashion retailing business at international levels and the association of the demographic profile to the intention of venturing into the fashion business in Malaysia and at the global market.